2004
DOI: 10.1007/s00418-004-0683-z
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of podocytes in a murine model of crescentic glomerulonephritis

Abstract: Recent observations suggest a central role of podocytes in crescent formation. In experimental glomerulonephritis podocytes disrupt the parietal epithelial layer and attach on its basement membrane, thus forming bridges between the tuft and Bowman's capsule, and they are a major constituent of crescents. In order to explain these findings we hypothesize that inflammation triggers motility in podocytes. In the present study we asked whether podocytes display alterations which suggest a migratory behavior in glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
4
15
0
Order By: Relevance
“…As has been shown in previous studies (1,(53)(54)(55), the process of tubular degeneration occurs in a certain sequence. First, cells simplify their structural elaborations, losing their surface differentia-…”
Section: Studies That Did Not Find Evidence For a Contribution Of Emtsupporting
confidence: 70%
“…As has been shown in previous studies (1,(53)(54)(55), the process of tubular degeneration occurs in a certain sequence. First, cells simplify their structural elaborations, losing their surface differentia-…”
Section: Studies That Did Not Find Evidence For a Contribution Of Emtsupporting
confidence: 70%
“…CD44 is a glycoprotein involved in cell adhesion, cell matrix interaction, and cell migration (17,18). Its expression by activated PECs points to a role for this adhesion molecule in the guided migration of PECs onto the glomerular tuft to replace injured/lost podocytes (16,19).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recent data have confirmed that podocytes also contribute to crescent formation in man, 4,5 although there is a great deal of heterogeneity in those affected, suggesting that in some cases local regulatory mechanisms fail to maintain a quiescent podocyte phenotype. Hence, modulation of podocyte phenotype may help the glomerulus to withstand inflammatory stress and to prevent, or arrest, the destructive process of crescent formation.…”
mentioning
confidence: 99%